Kinematics of elite unilateral below-elbow amputee treadmill-running - a case study - Mally, F.; Litzenberger, S.; Sabo, A. (Procedia Engineering, 2015)
Although scientists have already shown interest in the contribution of upper body movements (e.g. arm swing) to the biomechanics of running and walking, no study so far has investigated the influence of upper limb impairment on running or walking, respectively. Nevertheless, the International Paralympic Committee partly bases its classification system for athletes with unilateral through or above wrist impairment on research done with able-bodied subjects nearly three decades ago. Hence, in this study a high caliber male middle distance runner (age: 26 yrs., height: 183 cm, weight: 67 kg; personal bests: 400m: 0:48.45 min, 800m: 1:50.92 min, multiple medal winner at Paralympic Games, currently being classified as a T47 due to a missing right forearm from just a few centimeters below the elbow on) performed several trials without and with additional weight (0.5 kg, cu worn just proximal to the elbow joint) on the impaired arm at running speeds of 12, 16, 20 and 24 km/h on a treadmill. Concurrently a full-body motion analysis using a ten infrared camera Vicon motion analysis system was performed. Stance phase duration, arm swing velocity and angle between hip and shoulder axis were analyzed. It could be shown, that without weight stance phase duration for the right leg was highly significantly (alpha = 95%) longer at all running speeds than for the left leg, that arm swing velocity was faster for the right (impaired) arm. The hip-shoulder angle, however, did not show any significant difference for right or left side. Running with additional weight changed stance phase duration differences between left and right (not significantly), reduced the velocity differences between the impaired and sound limb (not significantly) and changed the rotation between hip and shoulder (significantly). The results of this study indicate that a missing upper limb affects running kinematics more clearly as hitherto assumed.